Sustainable Talent Management as a Strategy for Enhancing Organizational Competitiveness in a Dynamic Work Environment - Siti Mahmudah (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the influence of sustainable talent management on organizational competitiveness in a dynamic work environment. The research uses a quantitative approach with an explanatory research design. Data were collected through a survey using a structured Likert questionnaire involving 60 permanent employees with a minimum tenure of six months. The sampling technique employed purposive sampling. The collected data were analyzed using descriptive statistical analysis and simple linear regression to examine the relationship between the research variables. The results show that sustainable talent management has a positive and significant effect on organizational competitiveness (B = 0.63, t = 6.30, p < 0.001, R² = 0.41). Further analysis indicates that continuous competency development, talent retention, and employee well-being and engagement are positively associated with organizational competitiveness. These findings suggest that sustainable talent management can support improved productivity, innovation capability, and organizational adaptability in responding to changes in the work environment